Return to play after acute infectious disease in football players - Scharhag, J.; Meyer, T. (Journal of Sports Sciences, 2014)
Acute infectious diseases are common in athletes and can impair their ability to train and to compete. Furthermore, continuing exercise during infectious diseases may lead to prolongation or aggravation of illness with severe acute or chronic organ manifestations. Therefore, even simple infectious diseases require a sufficient period of convalescence and recovery, during which exercise may be not allowed. Nowadays, especially in professional football with high pressures on players, staff and clubs due to broad public interests as well as financial constraints, the return-to-play decision is of utmost significance. Based on previous suggestions and our own experience within amateur and professional athletes and football players, this article aims to give a short overview on return-to-play decisions after common acute infectious diseases in football players.